Optimalisasi Rute Pengiriman Finish Goods PT. SIWS dengan Menggunakan Metode Clarke And Wright - Indra Gumelar; Ima Gina Nurmala (LPPM, Sekolah Tinggi Teknologi DR. KHEZ Muttaqien, 2019)
This study aims to determine the route and scheduling of vehicles that can accommodate transportation problems from one source to the destination terminal nodes optimally by taking into account the distance and delivery time. The object of this research is automotive wiring harness company located in Purwakarta, Indonesia. The number of samples taken during the last one year is from 2017 until 2018, as many as twenty-one distribution points for consumer points. The Clarke and Wright Saving Heuristics method. From the study, it was concluded that the total distance traveled and the travel time that must be passed by trucking is 30 hours with a total of 1446 boxes of funneled.